Intraspecific phenotypic variation in nearly threatened mottled Nandus, Nandus nandus (Hamilton, 1822) - E-Mahfuj, Md. Sarower; Samad, Md. Abdus; Ahmed, Fee Faysal; Alim, Md. Abdul; Yosni Bakar; Simon Kumar Das (Penerbit Universiti Kebangsaan Malaysia, 2020)
Understanding intraspecific phenotypic plasticity is a prerequisite of stock identification, evolutionary studies, sustainable utilization, and fishery conservation. In this study, intraspecific phenotypic plasticity was assessed in terms of the external features (i.e. meristic, morphometric, and truss-based morphometrics) of the wild Nandus populations from four freshwater sources in Southwestern Bangladesh. Fish samples were collected from Arial Kha River, Madaripur (AKRM, n=26); Nabaganga River, Jhenaidah (NRJ, n=22); Bohnni Baor, Gopalganj (BBG, n=26); and Dhakuria Beel, Jashore (DBJ, n=22). Meristic, morphometric, and truss network data were subjected to one-way ANOVA followed by post hoc (Tukey-HSD) test. The meristic counts of all the samples demonstrated significant differences only in one of the six characters. By contrast, significant differences were observed in 8 morphometric characters and 31 truss network data from 16 morphometric characters and 35 truss network data, respectively. Principal component (PCA) and canonical variate analyses (CVA) were also performed on morphometric and truss-based network data. Meristic and morphometric results from PCA and CVA showed that populations were completely intermingled, forming a compact cluster within intrapopulation levels, while truss morphometric characters formed a separate cluster. Three dendrograms independently based on phenotypic relationships among the individuals of the four populations also confirmed the absence of phenotypic differentiation among the population due to clustering of different groups. The baseline information resulting from the current study would be useful for genetic studies and further in situ conservation of Nandus populations in Bangladesh.